Realitas Keagamaan dalam Fatwa MUI Nomor 2 Tahun 2022 tentang Uang Panai’: Analisis Filosofis terhadap Dinamika Sosial Masyarakat Suku Bugis Makassar - Idrus, Achmad Musyahid; Qayum, Abdul Rahman; Abbas, Rahmawati; Maulidah, Tahani Asri (Universitas Islam Negeri Alauddin Makassar, 2025)
The tradition of money panai in the marriage of the Makassar Bugis people not only reflects cultural values and family honor, but also gives birth to social dynamics and religious issues, especially in the practice of borrowing money from the family. This research aims to analyze in depth the religious reality surrounding the practice of money and identify the typology of Islamic law that arises from this phenomenon. The method used is a descriptive qualitative research with a philosophical and sociological approach, which focuses on the analysis of cultural practices in the local context of the Makassar Bugis community. Data were collected through participatory observation, in-depth interviews with traditional leaders, scholars, and couples who have experienced money loans, as well as documentation and normative literature reviews. The results of the study show that the practice of borrowing money has become a plural social reality and is even considered a pragmatic solution in meeting customary demands. However, this practice also raises complex legal problems, especially in the perspective of Islamic law. Normatively, a panai loan is categorized as mubah if it does not cause harm or burden the groom. On the other hand, this practice can be haram if it has implications for disproportionate economic pressure or is carried out with detrimental speculative intentions. These findings show that people's perceptions of Islamic law in the context of money are contextual and varied, depending on social motives, agreements between families, and locally applicable religious interpretations. This research emphasizes the need for a more adaptive approach to Islamic law to local traditions without ignoring the principles of justice and benefit.